2016
DOI: 10.1007/s11886-016-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Effectiveness of Ablation for Arrhythmias in the Congenital Heart Patients

Abstract: Arrhythmias are common in adults with congenital heart disease and account for a large proportion of hospitalizations. The complex anatomical heterogeneity, often in the presence of a delicate hemodynamic system, presents a significant electrophysiological challenge. This review outlines current clinical practice and advances in maximizing the effectiveness of ablation for arrhythmias in congenital heart patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
1
1
Order By: Relevance
“…These patients had more complex arrhythmias and substrates, which makes the procedure difficult and decreases the success rate. 13 However, the results of this study are superior to those reported in the literature. 14 In a recent report, Corcia et al 8 described Ebstein anomaly as a risk factor for failed ablation.…”
Section: Discussioncontrasting
confidence: 86%
“…These patients had more complex arrhythmias and substrates, which makes the procedure difficult and decreases the success rate. 13 However, the results of this study are superior to those reported in the literature. 14 In a recent report, Corcia et al 8 described Ebstein anomaly as a risk factor for failed ablation.…”
Section: Discussioncontrasting
confidence: 86%
“…The follow‐up period was relatively short for our cohort. However, as 75% of all recurrence occurred within the first year for previously published cohort, we believe presenting early recurrence could adequately reflect the effectiveness of our atrial tachyarrhythmia ablation in CHD. We encountered a higher recurrence of atrial tachyarrhythmia for our first few cases, and this is expected as CHD ablation and the use of the system required accumulation of experience.…”
Section: Discussionmentioning
confidence: 83%